Perlindungan Hukum terhadap Konsumen atas Perbuatan Melawan Hukum oleh Korporasi (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2026)
The rapid development of corporate business activities in Indonesia has contributed positively to economic growth; however, it also has the potential to cause losses to consumers. In practice, corporations often engage in unlawful acts that harm consumers, including violations of consumer rights, the provision of goods and/or services that do not meet required standards, and actions that contravene statutory regulations. This study aims to analyze the forms of legal protection for consumers as well as corporate liability for unlawful acts committed by corporations. This research employs a normative legal method with statutory and conceptual approaches. The legal materials used consist of primary, secondary, and tertiary sources, which are analyzed qualitatively. The findings indicate that legal protection for consumers has been regulated in various laws and regulations, particularly the Consumer Protection Law; however, its implementation still faces several challenges, such as weak law enforcement, low consumer awareness, and the complexity of proving corporate liability as a legal subject. Furthermore, corporate liability may be imposed through civil, criminal, and administrative sanctions depending on the nature of the violation committed. In conclusion, strengthening regulations and more effective law enforcement are necessary to ensure consumer protection from unlawful acts by corporations. In addition, enhancing the role of supervisory institutions and public legal awareness is essential to create a balance between the interests of business actors and consumers.